PROTECTION OF OWNERSHIP ACCORDING TO THE EUROPEAN CONVENTION ON HUMAN RIGHTS AND THE CONSTITUTION OF GEORGIA - Oniani, Nino (European Scientific Journal, ESJ, 2014)
According to John F. Kennedy: â€œthe right of each human being shall be violated when there is a danger of violating the right of a single human beingâ€ - call for the nation, June11, 1963. Nowadays, in Georgia as well as in the whole modern world, the rights to property is one of the most important rights, as this is one of the basis of the development of the country; this is why it is essential that such right be respected. The right to property is being regulated by the National Law of almost every country and by international treaties. Protection of private property is one of the main issues in the development of the liberal economy and in ensuring sustainable democratic, political and legislative systems, which shall serve the interests of the modern civilized society and the individual members of this society. In such system, the state has a role of guarantor to effectively use the right to property and it is not involved in free turnover of the property among the individuals. To put it otherwise, the function of the modern state is protection of property. Such modern state shall not fix useless restrictions and limitations on the rights of using property in a peaceful and effective manner, except for the cases, such restrictions and limitations are extremely necessary, proportional and are based on the law principles, which is a background for the effective use of the right to property.